Long-term darapladib use does not affect coronary plaque composition assessed using multimodality intravascular imaging modalities: a randomized-controlled study. Issue 2 (March 2018) - Choi, Woong Gil; Prasad, Megha; Lennon, Ryan; Gulati, Rajiv; Prasad, Abhiram; Lerman, Lilach O.; Lerman, Amir
Abstract : Background: Lipoprotein-associated phospholipase A2 (Lp-PLA2 ) may play a role in plaque progression and vulnerability. We aimed to define plaque characteristics on multimodality intravascular imaging in patients with coronary endothelial dysfunction in response to long-term inhibition of Lp-PLA2 by darapladib. Patients and methods: This is a double-blinded, randomized study screening 70 patients, and enrolling 54 patients with suspected ischemia, without obstructive disease on angiography and with coronary endothelial dysfunction by invasive assessment. Patients were randomized to receive darapladib or placebo for 6 months. Forty patients underwent multimodality intravascular imaging at baseline and after 6 months of therapy. Several parameters of plaque vulnerability were measured, including maximum value of lipid core burden index for any of the 4-mm segment (maxLCBI4 mm ) by near-infrared spectroscopy. Microchannels and macrophages were assessed using optical coherence tomography and necrotic core volume by virtual histology intravascular ultrasound. Results: There was no significant difference in maxLCBI4 mm [64.56 (7.74, 128.56) vs. 22.43 (0, 75.63), P =0.522] or in macrophage images angle [−9.5° (−25.53°, 12.68°) vs. −16.7° (−28.6°, −4.8°), P =0.489] between groups. There was a trend toward shorter microchannel length in the darapladib arm [0, (−4.4, 0.2) mm vs. 0.8 (−0.15, 1.9) mm, P =0.08]. Percentage of necrotic core volume was not significantly different. Conclusion: Thus, long-term inhibition of endogenous Lp-PLA2 activity with darapladib was not associated with a change in plaque progression and vulnerability indices after 6 months of therapy, and the endogenous Lp-PLA2 pathway may not play a direct role in the progression of early atherosclerosis in humans. Abstract : Supplemental Digital Content is available in the text.